Molecular hydrogen as a possible therapeutic factor in complex rehabilitation therapy in patients with muscular skeletal disorders (literature review) - Makolinets, Vasyl; Grashenkova, Tamara; Moseichuk, Volodymyr; Makolinets, Kyrylo; Moseichuk, Vladyslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
The paper presents an analysis of foreign scientific and medical data on the therapeutic factor — molecular hydrogen. The effectiveness of its application in the complex therapy of many diseases is revealed. The effect is achieved due to the small size of the molecule, which passes through biological membranes and inhibits dangerous free radicals in the mitochondria, as well as in the nucleus, which reduces the possibility of DNA damaging. Molecular hydrogen neutralizes oxidants in the brain due to its ability to cross the blood-brain barrier. It normalizes the functions and metabolic processes in the body and, as an antioxidant, is selective: it does not affect the useful free radicals involved in important metabolic processes and selectively eliminates only the most dangerous oxidants — hydroxyl radicals. Interacting with them, hydrogen converts them into water molecules without the formation of by-products and chain reactions. Unlike other known antioxidants, molecular hydrogen does not disrupt normal metabolism, does not cause negative changes in cells, activates the body’s own antioxidant systems. The possibility and expediency of the use of molecular hydrogen in the case of pathology of the musculoskeletal system has been confirmed. The peculiarities of its effect on bone and cartilage tissue in the experiment are shown. It has been determined that the use of molecular hydrogen is a new pharmacological strategy aimed at the selective removal of ONOO—, and can be an effective method in the treatment of joint diseases. Because cartilage receives nutrients through a diffusion-loading mechanism, and molecular hydrogen penetrates rapidly into tissues, it can be useful for the prevention of diseases of joints of degenerative origin. It reduces oxidative stress and slows down the reduction of matrix proteins and inhibition of proteinase degradation. Its effectiveness has been proven after injuries to the spinal cord, muscles and tendons, comorbid diseases such as hypertension, coronary heart disease, diabetes and metabolic syndrome. Key words. Molecular hydrogen, hydrogen water, hydrogen inhalations, joint diseases, consequences of musculoskeletal injuries, comorbid pathology.